MODIFICACION A LA TECNICA DE LA DOBLE IMPREGNACION ARGENTICA DE RIO-HORTEGA PARA LA DEMOSTRACION DE LAS FIBRAS PRECOLAGENAS - JARAMILLO, IGNACIO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1947)
Because of the lack of data about the essential amino acids in Mexican foods and the effect of ordinary cooking on their composition, and with a desire to contribute to available knowledge concerning the Mexican diet, 9 essential amino acids were detd in
BOL INST ESTUD MED BIOL
Keywords: TECNICA, IMPREGNACION, DEMOSTRACION, FIBRAS, PRECOLAGENAS; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA